Gas breakdown in DC electric field in a discharge tube with flat and conical cathodes - Lisovskiy, V.A.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2014)
This paper reports dc breakdown curves we registered between a flat anode and cathodes of various design: a flat one and cones of different height; the least inter-electrode distance was kept constant. We observed that the minima and the right-hand branches of breakdown curves coincided practically whereas the left-hand ones did not. At lower pressure values a divergence of left-hand branches of breakdown curves was registered for cathodes of different design. For conical cathodes the breakdown occurs either near its sharp tip or at the lateral surface of the cone at some distance from its tip. Измерены кривые зажигания разряда между плоским анодом и катодами разной геометрии – плоским и коническими различной высоты, при этом наименьшее расстояние между электродами сохранялось постоянным. Получено, что минимумы и правые ветви кривых зажигания во всех случаях практически наложились, различны были только левые ветви. При более низких давлениях наблюдается расхождение между левыми ветвями кривых зажигания для катодов различных геометрий. Для конических катодов пробой происходит вблизи их острия либо на боковой поверхности конуса на некотором расстоянии от его острия. Виміряні криві запалювання розряду між плоским анодом і катодами різної геометрії – плоским та конічними різної висоти, при цьому найменша відстань між електродами зберігалася постійною. Отримано, що мінімуми і праві гілки кривих запалювання у всіх випадках практично накладалися, різні були тільки ліві гілки. При більш низькому тиску спостерігається розбіжність між лівими гілками кривих запалювання для катодів різних геометрій. Для конічних катодів пробій відбувається поблизу їх вістря або на бічній поверхні конуса на деякій відстані від його вістря.